ANALISA TEMPORAL PERUBAHAN LUAS HUTAN MANGROVE DI KABUPATEN SIDOARJO DENGAN MEMANFAATKAN DATA CITRA SATELIT - Hidayah, Zainul (Bumi Lestari; Vol 13 No 2 (2013), 2012)
Abstract Mangrove forests are one of the coastal ecosystems that have significant ecological and economical value. This ecosystem is known for its role in protecting coastal environment against waves and storms as well as supporting the life of numerous marine organisms. However, the increase of human population and the need to expand settlements and industrial areas makes many mangrove ecosystems vulnerable. Objectives of this research were to measure the change of mangrove’s area of Sidoarjo district using satellite imagery data from different period and to classify the area based on their vegetation density. To measure the density of mangrove vegetation NDVI index were employed. Results of Landsat ETM-7 (acquisition 2002) and ALOS (acquisition 2010) analysis showed that mangrove’s area of Sidoarjo district has declined intensively. Illegal logging and land use changing were suggested to be the main cause of the destruction of mangrove forest in this area. In order to prevent further destruction of the mangrove’s area, local authorities have implemented UU No.27 where heavy penalties are implied for illegal logging.
Keywords: Key Words : Mangrove, NDVI, Sidoarjo, Satellite imagery data